FC 040INTERIM RESULTS OF PHASE 1 AND 2 TRIALS TO INVESTIGATE THE SAFETY, TOLERABILITY, PHARMACOKINETICS, PHARMACODYNAMICS, AND CLINICAL ACTIVITY OF BION-1301 IN PATIENTS WITH IGA NEPHROPATHY. (29th May 2021) - Barratt, Jonathan; Hour, Billy; Sibley, Cailin; Mittan, Angelique; Roy, Suzanne; Stromatt, Colleen; Endsley, Aaron; Lo, Jeannette; Glicklich, Alan
Abstract: Background and Aims: IgA nephropathy (IgAN), the leading cause of primary glomerulonephritis, is an autoimmune disease with no approved treatments. 1 Progression to end-stage-renal disease occurs in up to 45% of IgAN patients, requiring dialysis or kidney transplant to manage. 2-4 A critical step in IgAN pathogenesis is the production of galactose-deficient IgA1 (Gd-IgA1) leading to the generation of anti-Gd-IgA1 autoantibodies and the formation of immune complexes that result in kidney inflammation and damage. 5 A Proliferation-Inducing Ligand (APRIL), a soluble factor that regulates B cell differentiation, proliferation and survival of plasma cells, and IgA class-switching is elevated in patients with IgAN 6, 7 . IgAN patients with high plasma APRIL levels are reported as having higher levels of Gd-IgA1 and proteinuria and lower estimated glomerular filtration rates compared to those with lower plasma APRIL levels. 7 BION-1301 is a novel humanized blocking antibody targeting APRIL that has been evaluated in a Phase 1 study of healthy volunteers (HV). In Parts 1 and 2 of the Phase 1 study in HV, we previously reported that BION-1301 was well-tolerated with no serious adverse events (SAEs), a pharmacokinetic (PK) half life >30 days and demonstrated dose-dependent pharmacodynamic (PD) effects characterized by durable reductions in serum levels of free April (fAPRIL), IgA and Gd-IgA1, IgM, and to a lesser extent IgG 8 . Here we present interim results from Part 3 of the Phase 1 and the Phase 2 Open-Label Extension (OLE) trials that characterize the safety, PK and PD profile, and preliminary efficacy of BION-1301 in patients with IgAN. Method: The Phase 1 study (NCT03945318) comprises 3 parts. Parts 1 and 2 assessed single- and multiple ascending doses of BION-1301 in HV from 10mg to 1350mg and 50mg to 450mg once every 2 weeks for one month, respectively. Part 3 is an ongoing, open-label, two cohort design in approximately 20 IgAN patients with BION-1301 at a starting dose and regimen of 450mg once every 2 weeks for a total of 3 months. Key eligibility criteria for Part 3 include: (1) urine protein ≥0.5 g/24h or baseline UPCR ≥0.5 g/g, (2) stable/optimized dose of ACE-I/ARB or be intolerant to ACE-I/ARB, and (3) biopsy-verified diagnosis of IgAN within the past 10 years. Patients completing Part 3 are eligible to enroll in the Phase 2 OLE study (NCT04684745) to receive BION-1301 for up to an additional 2 years. To evaluate PK and PD effects of BION-1301, serum levels of BION-1301, free APRIL (fAPRIL), anti-drug antibodies (ADA), neutralizing antibodies (NAbs), and Gd-IgA1 were quantitated using ELISA-based immunoassays. Serum levels of IgA, IgG, and IgM were measured by immunoturbidimetry. UPCR was assessed from 24-hour urine collections. Results: In Part 3 of Phase 1 and the Phase 2 OLE trial to date, BION-1301 has been well tolerated in IgAN patients receiving a 450mg dose every two weeks for 12+ weeks with no SAEs observed. Consistent with PD responses previously reported in HVs, durable reductions in serum levels of fAPRIL and immunoglobulins were also observed in IgAN patients. Clinically meaningful reductions in proteinuria were observed as early as 12 weeks and were associated with the reduction in IgA. Additional data from patients receiving long-term treatment will be updated. Conclusion: BION-1301 is a novel humanized anti-APRIL monoclonal antibody being developed as a potential treatment for patients with IgAN. BION-1301 offers disease modifying potential by directly targeting the underlying multi-hit immune pathogenesis of IgAN, which is not addressed with the current standard of care treatment. Promising early biomarker and clinical activity responses support the continued development of BION-1301 in IgAN.